1995
DOI: 10.1046/j.1537-2995.1995.35195090661.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor screening for antibody to hepatitis B core antigen and hepatitis B virus infection in transfusion recipients

Abstract: Some 33 to 50 percent of cases of hepatitis B that could be transmitted by transfusion of blood from HBsAg-negative donors are prevented by anti-HBc screening. Anti-HBc-positive donors unequivocally positive for anti-HBs should be considered noninfectious for HBV and should be allowed to donate. Anti-HBc screening of paid plasmapheresis donors, supplemented by anti-HBs testing, would reduce the amount of HBV to be processed by virus inactivation and increase the content of anti-HBs in plasma pools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
131
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(140 citation statements)
references
References 41 publications
(1 reference statement)
6
131
1
Order By: Relevance
“…The elevated concomitant positivity for anti-HBc and anti-HBs was previously reported by Burrel (1980), Gonçales Júnior et al (1993), Barbara (1994) and Mosley et al (1995). These findings indicates a previous infection and immunity to HBV, although the degree of protection depends on the anti-HBs levels.…”
supporting
confidence: 56%
See 3 more Smart Citations
“…The elevated concomitant positivity for anti-HBc and anti-HBs was previously reported by Burrel (1980), Gonçales Júnior et al (1993), Barbara (1994) and Mosley et al (1995). These findings indicates a previous infection and immunity to HBV, although the degree of protection depends on the anti-HBs levels.…”
supporting
confidence: 56%
“…We found a low rate (1.9%) of anti-HBc among blood donors anti-HCV positive and Vasconcelos et al (1994) found (2.7%).The importance of anti-HBc as an alternative HCV marker has been questioned following the introduction of sensitive HCV tests for the screening of donors (Barbara 1994, Dodd 1995. However, it has been reported that anti-HBc screening can eventually prevent some HCV cases in high HBV prevalence areas (Mosley et al 1995). Jilg et al (1995) studying isolated anti-HBc individuals, found anti-HCV antibodies in 40.5%, of which 2/3 were HCV-RNA positive.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…The infectivity of blood donations containing anti-HBc as the only marker of HBV infection has been known for several decades and indicated that no more than 4% of recipients of anti-HBc-only blood developed HBV infection post-transfusion [31]. However, Mosley reported 17% infectivity of antiHBc-only blood products [22,32]. Anti-HBc screening has the potential of excluding the vast majority of occult HBV infection but this exclusion of anti-HBc positive donors is impractical in countries where HBV infection is prevalent and higher than 20% of the populations are anti-HBc positive [33].…”
Section: Discussionmentioning
confidence: 99%